Measuring red blood cell aggregation forces using double optical tweezers. (April 2013) - Fernandes, Heloise P.; Fontes, Adriana; Thomaz, André; Castro, Vagner; Cesar, Carlos L.; Barjas-Castro, Maria L.
Abstract Classic immunohematology approaches, based on agglutination techniques, have been used in manual and automated immunohematology laboratory routines. Red blood cell (RBC) agglutination depends on intermolecular attractive forces (hydrophobic bonds, Van der Walls, electrostatic forces and hydrogen bonds) and repulsive interactions (zeta potential). The aim of this study was to measure the force involved in RBC aggregation using double optical tweezers, in normal serum, in the presence of erythrocyte antibodies and associated to agglutination potentiator solutions (Dextran, low ionic strength solution [LISS] and enzymes). The optical tweezers consisted of a neodymium:yattrium aluminium garnet (Nd:YAG) laser beam focused through a microscope equipped with a minicam, which registered the trapped cell image in a computer where they could be analyzed using a software. For measuring RBC aggregation, a silica bead attached to RBCs was trapped and the force needed to slide one RBC over the other, as a function of the velocities, was determined. The median of the RBC aggregation force measured in normal serum (control) was 1 × 10−3 (0.1–2.5) poise.cm. The samples analyzed with anti-D showed 2 × 10−3 (1.0–4.0) poise.cm (p < 0.001). RBC diluted in potentiator solutions (Dextran 0.15%, Bromelain and LISS) in the absence of erythrocyte antibodies, did not present agglutination. High adherence was observed when RBCs were treated with papain. Results are in agreement with the imunohematological routine, in which non-specific results are not observed when using LISS, Dextran and Bromelain. Nevertheless, false positive results are frequently observed in manual and automated microplate analyzer using papain enzyme. The methodology proposed is simple and could provide specific information with the possibility of meansuration regarding RBC interaction.